Transactional Sex Among Men Who Have Sex With Men in Latin America: Economic, Sociodemographic, and Psychosocial Factors. - Oldenburg, Catherine E; Perez-Brumer, Amaya G; Biello, Katie B; Landers, Stewart J; Rosenberger, Joshua G; Novak, David S; Mayer, Kenneth H; Mimiaga, Matthew J (American journal of public health, 2015)
We assessed factors associated with engagement in transactional sex among men who have sex with men recruited from one of the largest Internet sites for men seeking social or sexual interactions with other men in Latin America.